Compatibility of elastomers in palm biodiesel - Haseeb, A.S. Md. Abdul; Masjuki, Haji Hassan; Siang, C.T.; Fazal, M.A. (Elsevier, 2010)
In recent time, environmental awareness and concern over the rapid exhaustion of fossil fuels have led to an increased popularity of biodiesel as an alternative fuel for automobiles. However, there are concerns over enhanced degradation of automotive materials in biodiesel. The present study aims to investigate the impact of palm biodiesel on the degradation behavior of elastomers such as nitrile rubber (NBR), polychloroprene, and fluoro-viton A. Static immersion tests in B0 (diesel), B10 (10 biodiesel in diesel), B100 (biodiesel) were carried out at room temperature (25 degrees C) and at 50 degrees C for 500 h. At the end of immersion test, degradation behavior was investigated by measuring mass, volume, hardness as well as tensile strength and elongation. The exposed elastomer surface was studied by scanning electron microscopy (SEM). Fourier Transform Infrared (FTIR) spectroscopy was carried out to identify the chemical and structural changes. Results showed that the extent of degradation was higher for both polychloroprene and NBR while fluoro-viton exhibited good resistance to degradation and was least attacked. (C) 2010 Elsevier Ltd. All rights reserved.